Unmasking the veil of PM2.5 pollution: A comprehensive analysis of health effects, economic losses, and environmental implications in North Indian States - Abhishek Dutta; Orathai Chavalparit (Ecotoxicology and Environmental Safety)
This research paper analyses particulate matter (PM2.5) pollution data from five Indian states to assess health impacts, including premature deaths from lung cancer (LC), chronic obstructive pulmonary disease (COPD), ischemic heart disease (IHD), stroke, and lower respiratory infections (LRI). Intake factors (iF), effect factors (EF), and characterization factors (CF) were used to quantify pollutant inhalation, health impact per unit intake, and potential health impact in Disability-Adjusted Life Years (DALYs), respectively. We found localities like Jahangirpuri in Delhi (DL) (3.25E-04–4.01E-04), Faridabad in Haryana (HR)(1.1E-04–9.59E-05), Bhiwadi in Rajasthan (RJ) (6.76E-05–9.73E-05), Ghaziabad in Uttar Pradesh (UP) (7.49E-05–1.32E-04) and Gobindgarh in Punjab (PB) (4.14E-05–5.16E-05) had much higher iFs than the previously reported pan- India value of 7.60E-06. Ghaziabad of UP recorded the highest EF of 4.02E+ 02 DALYs per kilogram PM2.5 inhalation in 2021. High iF and EF values resulted in alarmingly high CF values across all the monitoring stations of the states. The Jahangirpuri of DL recorded the highest CF of 9.88E+ 01 DALYs per kg of PM2.5. The combined five diseases PM2.5-induced mortality cases for five states were assessed to be 171,551 in 2019, which increased to 175,140 in 2022. UP had the largest share of combined mortality cases in 2022, where mortality cases due to stroke grew highest at 29.48 % during 2019–2022, followed by IHD (27.6 %), COPD (20.85 %), and LC (20.35 %). The study estimated economic loss from PM2.5 mortality for five diseases in five states from 2019 to 2022, ranging from 197,964 million US$ to 276,541 million US$. According to the research, the economic burden would still be worrisome if policy interventions can achieve a targeted 30 % PM2.5 reduction across five states by 2024. The study underscores the imperative need for a time-bound holistic approach to decimate air pollution in north Indian states.